A pilot investigation of feeding problems in children with esophageal atresia. Issue 3 (28th January 2014) - Baird, R.; Levesque, D.; Birnbaum, R.; Ramsay, M.
Summary While many long‐term complications of esophageal atresia (EA) have been well investigated, little is known about feeding difficulties in children after surgical correction of EA and its impact on caregivers. This study investigates the feeding behaviors of children with EA through a validated feeding questionnaire. The Montreal Children's Hospital Feeding Scale (MCH‐FS) was filled out by the primary caregiver during patient follow‐up visits in the multidisciplinary EA clinic. Demographic information, EA subtype, associated anomalies and outcomes were recorded. Results were compared between groups and to a normative sample. Thirty caregivers have completed the MCH‐FS; 26 patients had type C atresia (86.7%). In comparison to controls, 17.5% of EA cases are one standard deviation above the mean feeding difficulty score, while 6.7% (n = 2) cases are greater than two standard deviations above normative values. Typical EA patients (type C who were not born <30 weeks) had mean MCH‐FS scores in the subclinical range, whereas one extremely premature child and the patients with non‐type C EA (n = 4) all had scores in the severe range. Feeding difficulties of patients with typical EA appear mild. Likely explanations include the use of early protocolized care and intensive multidisciplinary care in follow up. Nonetheless, patients with complicated EA (non‐type C) and their caregivers tend to experience significant feeding difficulties. Early targeted care may be required for this patient subset, and additional cases will be investigated to confirm these preliminary findings and explore further risk factors of feeding problem in this cohort.